Delayed gangrenous penile necrosis following prolonged utilization of penile constriction ring - Nguyen, Vi; Garg, Nishant; Cedars, Benjamin E.; Puri, Dhruv; Ahmadieh, Kian; Buckley, Jill C. (Urology case reports, 2024)
Penile strangulation secondary to utilization of a constrictive ring is a rare urologic emergency that requires urgent decompression to prevent prolonged vascular obstruction resulting in necrosis and gangrene. Current literature is mainly comprised of case presentations that focus on management in the acute setting via removal of the ring. Herein, we describe surgical management of a patient who presents in delayed fashion after self-removal of the constrictive ring. We discuss our penectomy-sparing technique of debridement and split thickness skin graft.